Walras, Leontief, and the Interdependence of Economic Activities: Reply - Kuenne, Robert E. (Quarterly Journal of Economics, 1955)
Journal Article Walras, Leontief, and the Interdependence of Economic Activities: Reply Get access Robert E. Kuenne Robert E. Kuenne University of Virginia Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 4, November 1955, Pages 631–636, https://doi.org/10.2307/1882000 Published: 01 November 1955